IMPLEMENTASI KEBIJAKAN PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA SUNGAI PADUAN KECAMATAN TELUK BATANG KABUPATEN KAYONG UTARA - Juniarti E.01108034, Vevi (PublikA, Jurnal Ilmu Administrasi Negara, 2012)
AbstractThe title of this research is â€œPolicy Implementation Land and Building Tax Withholding di Desa Sungai PaduanKecamatan Teluk Batang Kabupaten Kayong Utaraâ€. The purposes of this research is to know and analyze howthe communication occurs between the texes collector and the tax payer in doing the socialitation about the ruleof PBB collecting in Desa Sungai Paduan and to analyze factor one of the problem in held collecting PBB taxeâ€™srule in Desa Sungai Paduan. Methot that being used to conduct this research is qualitative and the Edward IIItheory, that is about communication, resourees, disposotiuon, and the birocracy structure, but the theory used isonly about the communication and the resources. The result of this research shows that the communication thatoccuyrs between the taxes collector and the taxes payer is still not intensives so it causes the problem insocialization and it does not run effective. Moreover, the resources also becomes the problem in collecting thePBB taxes, including the finance that also influence the tools.Keywords: Policy Implementation, the PBB Collecting, and the Problem Factors.